Diffusion-weighted images (DWI) without ADC values in assessment of small focal nodules in cirrhotic liver - Chen, Mai-Lin; Zhang, Xiao-Yan; Qi, Li-Ping; Shi, Qing-Lei; Chen, Bin; Sun, Ying-Shi (Chinese Journal of Cancer Research; Vol 26, No 1 (February 27, 2014): Chinese Journal of Cancer Research, 2014)
Objective: To assess if diffusion-weighted magnetic resonance (MR) imaging without apparent diffusion coefficient (ADC) values provides added diagnostic value in combination with conventional MR imaging in the detection and characterization of small nodules in cirrhotic liver. Methods: Two observers retrospectively and independently analyzed 86 nodules (≤3 cm) certified pathologically in 33 patients with liver cirrhosis, including 48 hepatocellular carcinoma (HCC) nodules, 13 high-grade dysplastic nodules (HDN), 10 low-grade dysplastic nodules (LDNs) and 15 other benign nodules. All these focal nodules were evaluated with conventional MR images (T1-weighted, T2-weighted and dynamic gadolinium-enhanced images) and breath-hold diffusion-weighted images (DWI) (b=500 s/mm2). The nodules were classified by using a scale of 1-3 (1, not seen; 3, well seen) on DWI for qualitative assessment. These small nodules were characterized by two radiologists. ADC values weren’t measured. The diagnostic performance of the combined DWI-conventional images and the conventional images alone was evaluated using receiver operating characteristic (ROC) curves. The area under the curves (Az), sensitivity and specificity values for characterizing different small nodules were also calculated. Results: Among 48 HCC nodules, 33 (68.8%) were graded as 3 (well seen), 6 (12.5%) were graded as 2 (partially obscured), and 9 weren’t seen on DWI. Among 13 HDNs, there were 3 (23.1%) and 4 (30.8%) graded as 3 and 2 respectively. Five (50%) of 10 benign nodules were partially obscured and slightly hyperintense. For 86 nodules, the average diagnostic accuracy of combined DWI-conventional images was 82.56%, which was increased significantly compared with conventional MR images with 76.17%. For HCC and HDN, the diagnostic accuracy of combined DWI-conventional images increased from 78.69% to 86.07%. Conclusions: Diffusion-weighted MR imaging does provide added diagnostic value in the detection and characterization of HDN and HCC, and it may not be helpful for LDN and regenerative nodule (RN) in cirrhotic liver.